Recombinant human erythropoietin upregulates PPARγ through the PI3K/Akt pathway to protect neurons in rats subjected to oxidative stress. (23rd June 2022) - Wang, Huqing; Chen, Ming; Zhang, Tao; Gao, Zhen; Gong, Yu; Yu, Xiaorui; Wu, Haiqin
Abstract: In vitro cell experiments have suggested that recombinant human erythropoietin (rhEPO) and peroxisome proliferator activated receptor γ (PPARγ) activation exert protective effects on neurons. This study observed the learning and memory ability, antioxidant capacity and the ratio of apoptotic cells after rhEPO intervention and investigated the relationship among rhEPO, PI3K/Akt and PPARγ in the anti‐neural oxidative stress injury process in vivo. The results showed that rhEPO significantly improved the learning and memory abilities of rats subjected to oxidative stress, enhanced the antioxidant capacity of cells, and reduced neuronal apoptosis. Then, the PI3K/Akt and PPARγ pathways were inhibited, and TUNEL staining were used to observe the changes in the effect of rhEPO. After the PI3K/Akt and PPARγ pathways were inhibited, the effect of rhEPO on rats subjected to oxidative stress was significantly weakened, suggesting that both the PI3K/Akt and PPARγ pathways are involved in the process by which rhEPO protects neurons. Finally, Western blotting and immunofluorescence staining were used to observe the changes in PI3K/Akt and PPARγ signalling proteins in the neurons after the rhEPO intervention and to explore the relationship among the three. The results showed that rhEPO significantly increased the levels of the p‐Akt and PPARγ proteins and the level of the PPARγ protein in the nucleus, indicating that the PI3K/Akt pathway was located upstream of and regulates PPARγ. In conclusion, this study suggested that rhEPO activates the PI3K/Akt to upregulate PPARγ, enhance the cellular antioxidant capacity, and protect neurons in rats subjected to oxidative stress. Abstract : rhEPO reduces apoptosis and protects oxidative stress injury neurons by enhancing the antioxidant capacity of cells. PI3K/Akt and PPARγ pathways are involved in rhEPO‐protected neurons of rats subjected to oxidative stress. In this process, PI3K/Akt is located upstream of PPARγ pathway regulation.